LA COMPÉTENCE LINGUISTIQUE VS D’AUTRES COMPÉTENCES REQUISES DANS LA FORMATION PROFESSIONNELLE DES TRADUCTEURS SUR L’EXEMPLE POLONAIS - Tomaszkiewicz, Teresa (Neofilolog, 2019)
The purpose of the article is to present European norms aimed at improving the skills of translators working for various European Union Institutions. Although the norms have been widely discussed on the international level the author of the article feels that not all relevant information pertaining to the matter in hand may be known to the philologists worldwide. Therefore, the article provides further information on the criteria and puts special emphasis on discerning two basic aspects of improving translator's education; teaching translation competence as against developing linguistic competence.